The secret language of destiny: stress imprinting and transgenerational origins of disease - Zucchi, Fabiola C.; Yao, Youli; Metz, Gerlinde A. (Frontiers in Genetics, 2012)
Epigenetic regulation modulates gene expression without altering the DNA sequence to facilitate rapid adjustments according to current environmental conditions. The creation of an epigenetic memory allows that this information is passed on to subsequent generations. Here we propose that stress-induced genomic imprinting represents a critical determinant of health and disease across multiple generations. Epigenetic programming across generations may represent a key to understand adult-onset complex disease processes, propagation through generations and cumulative effects of life span and familial disease etiology. Ultimately, the mechanisms of generating an epigenetic memory may become of potentially promising diagnostic and therapeutic relevance. Exploring the role of environmental factors, such as stress, in causing variations in epigenetic profiles may lead to new avenues of personalized, preventive medicine based on epigenetic signatures and interventions.